1997
DOI: 10.1364/ol.22.000319
|View full text |Cite
|
Sign up to set email alerts
|

Theory of laser action in scattering gain media

Abstract: A laser model based on feedback produced by scattering has been developed to explain the narrow linewidth emission and input-output behavior observed in scattering gain media. The model is based on the transient two-level laser equations and includes the detailed spectral properties of the dye gain system. Monte Carlo methods were employed to calculate the threshold gain required for modeling the input-output and linewidth emission characteristics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
46
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(47 citation statements)
references
References 14 publications
1
46
0
Order By: Relevance
“…The stimulated emission in this case was enhanced through the use of TiO 2 nanoparticles. [23] Later that year, Tessler et al…”
Section: Historical Overview Of Lasing In Organic Materialsmentioning
confidence: 99%
“…The stimulated emission in this case was enhanced through the use of TiO 2 nanoparticles. [23] Later that year, Tessler et al…”
Section: Historical Overview Of Lasing In Organic Materialsmentioning
confidence: 99%
“…Ab-initio computational studies were limited to 1D and 2D geometries [27,28], not accounting for the critical character of three-dimensional (3D) localization [29]. Monte-Carlo simulations neglect interference effects [30,31,32]. Here we report on an original theoretical formulation; we quantitatively compare its predictions with experiments and with the first ever reported 3D+1 ab-initio MaxwellBloch simulations.…”
mentioning
confidence: 99%
“…These lasers can be tuned to emit different wavelengths by changing the concentration of the dye. A recent area of interest in the dye laser field is the introduction of a scattering media within the dye [108][109][110][111][112][113][114][115][116][117][118][119] . Several authors have found that scattering particles dispersed within a polymer gain media will increase intensity while decreasing the threshold and linewidth of the laser-action emission.…”
Section: Laser Dyes With Scatterersmentioning
confidence: 99%